Association of early feeding practices with dietary patterns of 7-year-olds from the birth cohort Generation XXI. (1st April 2022) - Barbosa, Catarina; Costa, Alexandra; Hetherington, Marion M.; Oliveira, Andreia
Abstract: Early feeding practices have been related to child's body mass index (BMI), however, their role in establishing dietary patterns is less well understood. The aim of this study was to examine the association of parent-reported early feeding practices (breastfeeding duration, type of foods and timing of complementary feeding) and dietary patterns identified at age 7 to explain BMI z-scores at 10 years of age. Participants were children from the Generation XXI cohort, evaluated at 4, 7 and 10 years of age (n = 3673). At 7 years-old, dietary intake was assessed with a validated food-frequency questionnaire. Two dietary patterns were previously derived: "Energy-dense foods" (higher in energy-dense foods, and lower in vegetable soup, significantly associated with BMI z-score at 10 years-old, and the "Fish-based" dietary pattern (higher in fish consumption and low in energy-dense foods). Adjusted sex-stratified associations were estimated by generalized linear models. Boys and girls who were never breastfed or were breastfed for a very short duration had lower scores in the "Fish-based" dietary pattern, compared to those with longer breastfeeding durations (Boys: β = −0.219; 95%CI: 0.361; −0.077; Girls: β = −0.223; 95%CI: 0.358; −0.088). No significant associations between breastfeeding and the "Energy-dense foods" dietary pattern were found. Boys and girls who were offered cereals as a first food during complementary feeding, in comparison with soup, presented lower scores in the "Energy-dense foods" dietary pattern (Boys: β = −0.183; 95%CI: 0.292; −0.074; Girls: β = −0.155; 95%CI: 0.259; −0.050), but only girls presented higher scores in the 'Fish-based' dietary pattern (β = 0.137; 95%CI: 0.006; 0.267). The age of introduction of complementary feeding was not significantly associated with the dietary patterns. Parents should be supported in their infant feeding decisions, given the potential effects of breastfeeding duration and first foods at complementary feeding on shaping longer term dietary patterns of young children.